Understanding the public and common good in the contemporary environmental policy - Nadić, Darko (Sociološki pregled, 2022)
In this paper, the idea of the public and common good is analyzed from the standpoint of the environmental policy as a sort of public policy. The analysis and considerations start from the postulate that public goods in the academic public are most commonly observed as natural resources and that their function is to be used for economic and particularly industrial development. What needs redefining, and what should be changed by the environmental policy, is taking the status of the public good to a higher status, having in mind its general characteristic – irreversibility. That dimension of the future to be possessed by the public good is the basis for the survival of the modern society. The work illustrates the distinction of the idea of the public and common good in practice using the example of the Republic of Serbia in the case of the environmental-political problem caused by the construction of a mini-hydropower plant, i.e. the administrative management of the public and common good.
Keywords: public good; common good; environmental policy; quality of life; sustainable development